Inovações disruptivas e economia compartilhada: - Barros, Wallas Bruno da Silva (Universidade Federal do Tocantins, 2022)
nnovation is a key element for organizations that seek to differentiate themselves from their competitors and obtain a competitive advantage. Disruptive innovations create something simple, easy to use, convenient and accessible, which in many cases are capable of destabilizing the dominant competitors of a given market, such as the Uber application, which in addition to reaching its direct competitors, taxi drivers, also offer differentiated services. Among the differentiated services offered by Uber is the sharing of services, which allows the user to share transportation costs, through the shared economy. In this perspective, this study aims to describe the Uber case in the city of Araguaína, as a disruptive technology and shared economy. With descriptive analysis from the perspective of the user of this application, it is pointed out by means of a closed questionnaire, whether the Uber user in Araguaína perceives the application as a disruptive innovation and a shared economy mode capable of destabilizing its market-leading competitors. The results show that Uber through its usability, demonstrates to be an easy to use, convenient and accessible application, that provides better services when compared to taxis and that brings many benefits to its supporters